KONSTRUKSI HUKUM PEMBIAYAAN INFRASTRUKTUR BERBASIS KERJASAMA PEMERINTAH BADAN USAHA (KPBU) UNTUK MEWUJUDKAN KETAHANAN NASIONAL - M. Rifqinizamy Karsayuda; Moh Fadli; Moh Khusaini; Adi Kusumaningrum (CV. AFDIFAL MAJU BERKAH, 2023)
Indonesia requires substantial infrastructure investments. The government can only provide less than half of the total funding required for strategic infrastructure investments from 2019 to 2024. Therefore, the government needs to explore alternative funding sources to meet its infrastructure needs. Public-Private Partnership (PPP) through the Government Business Entity (KPBU) presents itself as an alternative infrastructure financing solution that involves collaboration between the government and the private sector. Through the legal construction method using qualitative analysis techniques, the research found that the alternative approach to infrastructure financing through state-owned PPP is a public-private partnership with non-conventional financing instruments. This approach accelerates infrastructure development, increases resource efficiency, and requires strong regulation and supervision. The government needs to oversee the use of public funds, selection of private partners, and risk control in PPP projects. Improved transparency, coordination, and capacity of the government and private partners are key to the success of such projects.